The Association of the Potential Risk Factors and Nutrition Elements with Abortion and Calving Rates of Egyptian Buffaloes (Bubalus bubalis) - Walaa M. Essawi; Ali Ali El-Raghi; Fatma Ali; Mohamed A. Nassan; Ahmed N. F. Neamat-Allah; Mahmoud A. E. Hassan (Animals, 2021)
The aim of the present study was to investigate risk factors, serum minerals, and metabolites associated with non-infectious abortion and calving rates of Egyptian buffaloes. Data were obtained from 364 pregnant buffaloes of different ages and parities over 7 years from 2014 to 2020. Body condition score (BCS) was a risk factor regarding abortion and calving; the thinnest buffaloes were more likely to abort and less likely to calving than those with body energy reserves. In comparison with the spring season, aborting probability decreased 49.7% the odds ratio (OR = 0.503), while the chance of calving increased 72.1% (OR = 1.721) during winter. The parity was another significant factor related to abortion and calving rates; multiparous buffaloes were less likely to abort and more likely to calving than primiparous. Dry buffaloes had 88.2% (OR = 0.118) lesser odds of abortion and six times (OR = 6.012) more likely to give birth than those lactating. The sex of the fetus was not a risk factor regarding abortion or calving. Other variables significantly associated with abortion rate were glucose and copper in the sera of aborted buffaloes were significantly higher (p < 0.05), and those of urea, uric acid, total protein, total cholesterol, phosphorus, magnesium and iron were significantly (p < 0.05) lower than a normal pregnancy. In conclusion, the present results emphasize that the identification of the risk factors, serum minerals and metabolites associated with fetus abortion of Egyptian buffalo may provide useful information, which assists to construct suitable preventive measures to raise reproductive performance.